Kolaviron attenuates cardiovascular injury in fructose-streptozotocin induced type-2 diabetic male rats by reducing oxidative stress, inflammation, and improving cardiovascular risk markers - Jeffrey O. Adoga (Elsevier, 2021)
The prevalence of cardiovascular disease among type-2 diabetic patients has become a source of major concern world over. This study explored the protective effect of kolaviron, a bioflavonoid, against oxidative cardiovascular injury in fructose- streptozotocin-induced type 2 diabetic male Sprague Dawley rats. After acclimatization, induction, and confirmation of type-2 diabetes, kolaviron was administered for 28days, after which the animals were anesthetized with Isofor and euthanized. Blood from each rat were collected, and blood samples were then centrifuged for serum and plasma. Cardiac troponin I (cTnI), creatine kinase myocardial band (CK-MB), Creatine phosphokinase (CK), and insulin levels were immediately determined in serum, while remaining samples (serum, plasma, and organs) were stored in the bio-freezer at − 80 °C and 10% formalin for enzyme-link immunosorbent assay (ELISA), biochemical, molecular, and histopathological studies. The results show that type-2 diabetes induction with fructose and streptozotocin led to increased blood glucose levels, decreased insulin levels and cardiac antioxidant enzyme activities, increased malondialdehyde levels, cardiac biomarkers and pro-inflammatory cytokines levels, resulted in abnormal lipid profile, increased blood pressure and angiotensin-converting enzyme (ACE) activity, and decreased plasma endothelial nitric oxide synthase (eNOS) concentration. The histopathological examination of the cardiac tissue revealed severe lesion, hypertrophy, and myofibrils degeneration. However, administration of kolaviron for 28days remarkably improved these conditions. Hence the result from the study validates the potency of kolaviron, and suggests it could serve as an alternative to existing remedy in ameliorating or protecting against cardiovascular injury in type-2 diabetes.